2016
DOI: 10.1002/ajoc.201600300
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1 α‐ and 1 β‐amino‐25‐hydroxyvitamin D3

Abstract: 1a-Amino-25-hydroxyvitamin D 3 is of interest because of its low calcemic effect in vivo comparedt o1 ,25-dihydroxyvitamin D 3 and its characteristicinhibitory activity towards sterol regulatory elementb inding protein (SREBP), aregulator of lipogenesis. Here we describe the construction of an ovel A-ring synthon bearing an allylic amine, in which the key reaction is an Ichikawa rearrangemento fa llyl cya-nate generated from an allylic alcohol, which wasd erived from l-malic acid. The diastereomers were separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In our effort to delineate VD 3 activity, we initially searched for VD 3 analogs that activate VDR but lack SREBP inhibitory activity. An in-house library of 250 vitamin D congeners was screened for their ability to inhibit the activity of an SREBP-responsive luciferase reporter, in which expression of luciferase is controlled by three SREBP binding sites. We found that a series of vitamin D analogs, bearing alkyltriazole and alkyltetrazole substituents at C2 ( 4 – 9 ) (Figure ), displayed limited SREBP inhibitory activities (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…In our effort to delineate VD 3 activity, we initially searched for VD 3 analogs that activate VDR but lack SREBP inhibitory activity. An in-house library of 250 vitamin D congeners was screened for their ability to inhibit the activity of an SREBP-responsive luciferase reporter, in which expression of luciferase is controlled by three SREBP binding sites. We found that a series of vitamin D analogs, bearing alkyltriazole and alkyltetrazole substituents at C2 ( 4 – 9 ) (Figure ), displayed limited SREBP inhibitory activities (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…The relevance of this short pathway to 1,25D 3 analogs has been demonstrated by the intense synthetic activity used for the preparation of substituted A-ring-enyne synthons [68][69] and vitamin D analogs modified at the A-ring. [70][71][72][73][74][75][76][77][78][79][80] The relative high temperature (reflux in triethyl amine-toluene) required for the Pd(0)-catalyzed alkylative cyclization is unsuitable for the formation of vitamin D analogs that undergo thermal equilibration to the previtamin D form such as 6-methyl-25hydroxyvitamin D 3 , [43,81] and aromatic-D-ring analogs. [44,45]…”
Section: The Pd(0)-catalyzed Alkylative-cyclization Approach (G)mentioning
confidence: 99%